Hubungan Temperatur dan Hemoglobin dengan Kejang Demam di RSUD Abdoel Wahab Sjahranie Samarinda - Alfina Mapalidara (Jurnal Medika : Karya Ilmiah Kesehatan, 2022)
Febrile seizure is the most common neurological disorder in children. Several risk factors were included for febrile seizure, namely temperature and hemoglobin. The purpose of this study was to determine the relationship between temperature and hemoglobin with febrile seizure. This study used analytical observational method with a case-control approach. Data were taken from inpatient medical records at the Abdoel Wahab Sjahranie Hospital in Samarinda from the period of 2020 – 2022 using the purposive sampling technique. Ninety-eight data were obtained from medical records, consisting of 49 patients with febrile seizure and 49 patients with fever without seizure who were hospitalized. The statistical analysis used Spearman's Correlation Test for temperature and Chi-square Test for hemoglobin, p-value<0.05 was considered significant. The results of the analysis of the relationship between temperature and febrile seizures showed p = 0.000; r = 0.374. The relationship between hemoglobin and febrile seizures showed p = 0.011; OR = 4.963. It was concluded that temperature and hemoglobin, each had a significant relationship with febrile seizure.